(untitled) (KULT_online, 2009)
Over the course of 24 essays, the volume Das Amerika der Autoren. Von Kafka bis 09/11 explores the dynamic between 20th century German-speaking authors and the American mythos. The volume, published by Jochen Vogt and Alexander Stephan, visits noteworthy moments in the German literary discourse on America, taking Kafka’s novel Amerika as its starting point and continuing through to literary treatments of 9/11. By identifying a traceable ambivalence towards the United States that swings between admiration and rejection, the volume is an up-to-the-moment contribution to the study of transatlantic relations as they are reflected in culture.